Long Term Survival and Limb Salvage in Patients With Non-Revascularisable Chronic Limb Threatening Ischaemia. (August 2021) - Verwer, Maarten C.; Wijnand, Joep G.J.; Teraa, Martin; Verhaar, Marianne C.; de Borst, Gert J.
Abstract : Objective: The aim of this study was to provide long term survival and limb salvage rates for patients with non-revascularisable (NR) chronic limb threatening ischaemia (CLTI). Methods: This was a retrospective review of prospectively collected data, derived from a randomised controlled trial (JUVENTAS) investigating the use of a regenerative cell therapy. Survival and limb salvage of the index limb in CLTI patients without viable options for revascularisation at inclusion were analysed retrospectively. The primary outcome was amputation free survival, a composite of survival and limb salvage, at five years after inclusion in the original trial. Results: In 150 patients with NR-CLTI, amputation free survival was 43% five years after inclusion. This outcome was driven by an equal rate of all cause mortality (35%) and amputation (33%). Amputation occurred predominantly in the first year. Furthermore, 33% of those with amputation subsequently died within the investigated period, with a median interval of 291 days. Conclusion: Five years after the initial need for revascularisation, about half of the CLTI patients who were deemed non-revascularisable survived with salvage of the index limb. Although the prospects for these high risk patients are still poor, under optimal medical care, amputation free survival seems comparable with that of revascularisable CLTI patients, while the major amputation rate within one year, especially among NR-CLTI patients with ischaemic tissue loss, is very high.